Career Choices and the Evolution of the College Gender Gap - Rossi, Martin A. (Published by Oxford University Press on behalf of the World Bank, 2019)
The opportunity cost for men of pursuing a college degree has been rising due to the increase in the rewards to becoming a superstar in occupations typically dominated by men, like professional sports. This suggests a novel explanation for the evolution of the college gender gap (which shows a clear upward trend in female college enrollments relative to male enrollments). Causal evidence from a natural experiment in European soccer markets—that provides exogenous variation in the expected earnings for men associated with a superstar path—supports this explanation: an increase in male earnings has a significant positive effect on the ratio of female to male tertiary enrollment in college education. Results are robust to using different samples of countries, to allowing for regional time trends, to analyzing lagged effects, to changing the definition of the treatment, and to exploiting alternative definitions of exposure.